Foreign direct investment entry mode and China’s carbon productivity based on spatial econometric model - Tang, Decai; Yi, Rui; Kong, Haojia; Da, Dan; Boamah, Valentina (Frontiers in Environmental Science, 2022)
As the world's largest developing country and the largest carbon emitter, China must consider economic growth and carbon emission reduction in the process of development. Therefore, improving carbon productivity is an important goal of China at present. At the same time, China's foreign capital inflow has always been at the forefront of the world, and foreign direct investment (FDI) has had various impacts on China's carbon productivity. Based on the panel data of 25 provinces in China from 2007 to 2019, this paper uses a spatial econometric model to study the difference in the impact of FDI on China's carbon productivity under different entry modes. The study found that: when FDI enters China in the mode of a joint venture, there is a positive spatial spillover effect, which is conducive to improving China's carbon productivity; while when FDI enters China in the mode of a wholly foreign-owned enterprise, there is a negative spatial spillover effect, which will inhibit the improvement of China's carbon productivity. Therefore, when introducing foreign capital, the Chinese government should formulate differentiated foreign investment policies according to the different entry modes of FDI and encourage more FDI to enter China in joint ventures.